Lignin as Alternative Reinforcing Filler in the Rubber Industry: A Review - Mohamad Aini, Nor Anizah; Othman, Nadras; Hussin, M. Hazwan; Sahakaro, Kannika; Hayeemasae, Nabil (Frontiers in Materials, 2020)
Lignin has a potential reinforcing filler and alternative to carbon black in rubber industry. This is due to cheaper materials, abundant with yearly renewable source, low weight, high biological efficiency and wide ecological adaptability. Utilization of bio-filler in rubber industry has increased more attention among the researchers due to increasing environmental concerns and toxicological effect of carbon black towards health and environment. This article is intended to summarize the current efforts in development of green and sustainable of rubber product. Instead of focused to silica and alternative rubber matrix like guayule and Russian dandelion, lignin also has potential as reinforcing filler and lead to development of competitive green rubber composites. Lignin has several special properties such as good mechanical, physico-chemical, biodegradability, antioxidant and excellent thermal stability. However, incorporation of lignin in rubber matrix is not a straightforward and needs to overcome with certain suitable solution because of the polarity of lignin molecules which contribute to strong self-interactions. Consequently, chemical modification of lignin is often used to improve the dispersion of lignin in elastomers, or compatibilizer is added to enhance interfacial of adhesion between lignin and rubber matrix. This review attempts to compile relevant knowledge about the performance of lignin-filled rubber composite from different approach such as mixing method, surface modification, hybrid filler etc. This study is expected to gain significance interest of researcher globally on the subject of lignin-based rubber composites and the advancement of development in green rubber product.